Synthesis, structure and antiferromagnetic behaviour of brannerite MnV2O6 - 周传仓 刘发民 丁芃 蔡鲁刚 钟文武 张嬛 (Chinese physics B, 2010)
Brannerite MnV2O6 with plate-like shape is successfully synthesized by hydrothermal method. Its crystal structure and morphology are investigated by x-ray diffraction （XRD）, scanning electron microscopy （SEM）, transmission electron microscope （TEM）, high resolution transmission electron microscopy （HRTEM） and select area electronic diffraction （SAED）. The results show that the brannerite MnV2O6 with monoclinic structure has a uniform plate-like shape with a diameter of about 5-8μm and a thickness of about 500 nm. SAED patterns further confirm the structure of the brannerite MnV2O6 and the single crystalline character of the plate crystal. Magnetic properties are measured by superconducting quantum interference device （SQUID） in a temperature range of 2-300 K under a magnetic field of 1 T. The magnetic measurement results indicate that the material undergoes an antiferromagnetic transition with a Neel temperature of 17 K. Above 50 K, the inverse susceptibility is fitted well to the Curie-Weiss law with a calculated moment of 5.98μB. Finally, the origin of antiferromagnetic behaviour in the brannerite MnV2O6 is explained by means of Anderson model.